A NEW METHOD FOR ESTIMATING INCREASE IN RADIATION DOSE ASSOCIATED WITH IODINATED CONTRAST USE. Issue 5 (4th April 2022) - Wang, Qiang; Fu, Qiang; Pang, Cong
Abstract: This work investigates the impact of iodinated contrast medium (ICM) on radiation dose in computed tomography (CT) scans using linear models established through a phantom study. Thermoluminescence dosemeters (TLDs) were calibrated using semi-conductor X-ray dosemeters. An electron density phantom, with a vial containing TLDs and different concentrations of iodinated blood, were scanned at different tube voltages. Irradiated TLD outputs were measured and absorbed dose to iodinated blood calculated. CT numbers (tissue attenuation as measured by Hounsfield units) were plotted against absorbed doses to obtain linear models. Data from 49 real patient scans were used to validate the linear models. At each X-ray energy, CT numbers were linearly correlated with the absorbed doses, that is with the increase of blood iodine concentration, the CT number increased and the absorbed dose increased accordingly. ICM can cause an increase of organ dose; the average dose increases were 31.8 ± 8.9% for thyroid, 37.1 ± 9.2% for cardiac muscle, 77.7 ± 14.0% for cardiac chamber, 7.1 ± 2.3% for breast, 26.1 ± 7.3% for liver, 39.8 ± 11.8% for spleen, 96.3 ± 12.2% for renal cortex and 82.4 ± 11.6% for medulla nephrica. ICM used in enhanced CT scan resulted in increased organ doses. Our models for estimating organ dose based on CT number were established by experiment and verified in clinical use.